2020
DOI: 10.3390/cancers12071927
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Basis of Heterogeneous NK Cell Responses against Acute Leukemia

Abstract: Natural killer (NK) cells are key cytotoxic effectors against malignant cells. Polygenic and polymorphic Killer cell Immunoglobulin-like Receptor (KIR) and HLA genes participate in the structural and functional formation of the NK cell repertoire. In this study, we extensively investigated the anti-leukemic potential of NK cell subsets, taking into account these genetic parameters and cytomegalovirus (CMV) status. Hierarchical clustering analysis of NK cell subsets based on NKG2A, KIR, CD57 and NKG2C markers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…Several studies reported that ALL blasts are not effectively killed by NK cells in vitro [ 115 , 116 , 117 , 118 ]. Although the reasons are not yet precisely understood, it is known that developing leukemia modifies NK cells’ education and maturation.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that ALL blasts are not effectively killed by NK cells in vitro [ 115 , 116 , 117 , 118 ]. Although the reasons are not yet precisely understood, it is known that developing leukemia modifies NK cells’ education and maturation.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…The molecular basis for the NK cells’ alloreactivity is the recognition of specific ligands for NK cell activating receptors and lack of recognition by the inhibitory receptors (“missing-self” reactivity) [ 64 ]. Research from the last decade provides information how HLA and KIR genotypes of the donors shape NK cell repertoire and alloreactivity of NK cells [ 117 ]. Pende et al presented that the activating receptor KIR2DS1, which recognizes HLA-C2 alleles on ALL cells, plays a major role in the lysis of leukemia cells by donor NK cells [ 130 ].…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…More importantly, tumor cells expressing KIRs ligands may inhibit the functions of some NK cell subsets via inhibitory KIRs. Additionally, it was observed that there was a broad inter-individual disparity in NK cell response against the same target as reported by Makanga et al (64). Therefore, in order to guide the selection of suitable NK subtypes from different donors, it is necessary to have a deeper understanding of the relationship between NK receptors and tumors.…”
Section: Other Types Of Cells Instead Of Ab-t Cellmentioning
confidence: 88%
“…Makanga et al. demonstrated that CD57 + and KIR + NK cells from healthy individuals exhibited the highest degree of cytotoxicity against AML blasts, while ALL targets were less susceptible to KIR + NK subsets compared with NKG2A + NK subsets ( 36 ). On the basis of previous studies, we hypothesize that KIR may have a minor impact on the elimination of lymphoblastic leukemias, and patients with myeloid disease are more likely to benefit from well KIR-educated NK cells.…”
Section: Discussionmentioning
confidence: 99%